Walking Tour and Culture: Fostering Cultural Collaboration Through Tourism - Febriani, Prita; Muttaqin, Islakhul (CV. Austronesia Akademika, 2025)
Indonesia’s rich cultural diversity, encompassing over 300 ethnic groups and more than 700 local languages, presents immense potential for the development of culture-based tourism. However, this cultural wealth faces increasing threats from modernization, urbanization, and globalization, which contribute to the erosion of traditional values and local identity. One promising solution to counteract these challenges is the implementation of walking tours, which offer immersive and educational tourism experiences that foster deeper cultural appreciation while empowering local communities. This study aims to explore how walking tours can function as effective instruments for cultural preservation and community-based tourism development in Indonesia. Employing a qualitative approach through literature review, the research analyzes secondary data from academic publications, policy reports, and case studies focusing on walking tour practices in various Indonesian cities and cultural villages. The findings reveal that walking tours provide significant benefits, including the revitalization of local wisdom, economic opportunities for artisans and small businesses, and increased tourist awareness of cultural sustainability. Moreover, the role of trained local tour guides is pivotal in facilitating authentic and meaningful interactions between tourists and host communities. These tours contribute not only to visitor satisfaction but also to the strengthening of cultural identity and community resilience. In conclusion, walking tours serve as a strategic model for integrating cultural education, tourism, and community empowerment.